(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Gender plays a most important role in a person’s life. Gender issues are reflected in the plays of Vijay Tendulkar and Girish Karnad. They present a realistic picture of the plight of women in the society. How the fate of a person is affected by his/her gender? First of all, the plays of Vijay Tendulkar are discussed in the light of gender issues and then Girish Karnad’s.The word gender comes from the Middle English word ‘gendre’ which is a derivation of the Latin word ‘genus’. Both the words ‘gendre’ and ‘genus’ mean ‘kind’, ‘type’ or ‘sort’. The Oxford Dictionary defines gender, “as the fact of being male or female” . Linda L. Lindsey points out about gender in the book titled Gender Roles: A Sociological Perspective, “Gender refers to those social, cultural and psychological traits linked to males and females through particular social context”.